A study for profiling mathematics teachers regarding factors affecting promotion of students metacognition - Şeker, Vuslat. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
The main objective of this study was to describe mathematics teachers’ profiles on factors affecting their promotion of students’ metacognition through developing profiling tools. In the light of this aim, four factors from the Framework for Analysing Mathematics Teaching for the Advancement of Metacognition -FAMTAM- (Ader,2009) were used. The factors were (1) teachers’ conceptualization of metacognition, (2) teachers’ perceptions of students’ features and needs, (3) distribution of mathematical authority in the classroom and (4) the external pressure perceived by teachers. The Teachers’ Conceptualization of Metacognition Scale, the Teachers’ Perceptions of Students’ Features and Needs Scale, the Distribution of Mathematical Authority Scale and the External Pressure Perceived by Teachers Scale were developed to reach the aim of the study. The sample consisted of 314 middle and secondary school mathematics teachers. In this study, descriptive, correlational and causal comparative research designs were used. Descriptive statistics were done to explain mathematics teachers’ current thoughts on four factors. Correlational analyses were done to investigate the relationships between four factors. Group comparisons based on gender, age, education level, years of experience, teaching level and school types were examined. The results showed that most mathematics teachers conceptualized metacognition in accordance with the commonly accepted conceptualizations in the literature. They were aware of students’ features and needs. They supported a learning environment where mathematical authority was exercised by students. However, they perceived high external pressure from various factors influencing their promotion of students’ metacognition. Moreover, significant gender differences were observed on teachers’ claims about their distribution of mathematical authority, perceived external pressure and conceptualization of metacognition in favor of female teachers. Significant differences according to age and years of experience were observed only on teachers’ distribution of mathematical authority in favor of teachers with 20-29 age group and 1-5 years of experience respectively. There were also significant differences on distribution of mathematical authority and perceived external pressure according to teachers’ educational background. Teachers with a master’s degree supported the distribution of mathematical authority more and perceived less external pressure than teachers with a bachelor degree. In addition, significant teaching level differences were found on each factor in favor of middle school mathematics teachers. Lastly, perceived external pressure and teachers’ conceptualization of metacognition also significantly differed on school types. Teachers working at a public school perceived higher external pressure and their conceptualization of metacognition’s scores were lower than teachers working at a private school. Implications of the findings and potential ways forward for making better sense of teachers’ considerations for promoting metacognition are discussed.
Keywords: Mathematics teachers.; Metacognition.; Mathematics -- Study and teaching.; Problem solving in children